2017
DOI: 10.3389/fphar.2017.00295
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone as a Potential Adjuvant Therapy for Cancer Treatment: Evidence from Preclinical Studies

Abstract: Thymoquinone (TQ), the main bioactive component of Nigella sativa, has been found to exhibit anticancer effects in numerous preclinical studies. Due to its multitargeting nature, TQ interferes in a wide range of tumorigenic processes and counteracts carcinogenesis, malignant growth, invasion, migration, and angiogenesis. Moreover, TQ can specifically sensitize tumor cells toward conventional cancer treatments (e.g., radiotherapy, chemotherapy, and immunotherapy) and simultaneously minimize therapy-associated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 97 publications
3
67
0
Order By: Relevance
“…The downregulation of STAT3 activation was associated with a reduction in JAK2 and c-Src activity (Zhu et al, 2016). Recent preclinical studies suggested the potential of TQ in adjuvant therapy with other chemotherapeutic agents (reviewed in Mostofa et al, 2017). In another study in BALB/c mice transplanted with mouse epithelia breast cancer EMT6/P cell line, TQ in combination with melatonin significantly decreased the tumor size, induced tumor cell death, decreased VEGF expression, and activated anticancer immune response by increasing serum interferon (INF)-g level (Odeh et al, 2018).…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…The downregulation of STAT3 activation was associated with a reduction in JAK2 and c-Src activity (Zhu et al, 2016). Recent preclinical studies suggested the potential of TQ in adjuvant therapy with other chemotherapeutic agents (reviewed in Mostofa et al, 2017). In another study in BALB/c mice transplanted with mouse epithelia breast cancer EMT6/P cell line, TQ in combination with melatonin significantly decreased the tumor size, induced tumor cell death, decreased VEGF expression, and activated anticancer immune response by increasing serum interferon (INF)-g level (Odeh et al, 2018).…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…There are some reported studies on the anticancer efficacy of Tq. Recent reports suggest Tq to be effective in adjuvant cancer therapies (Mostofa, Hossain, Basak, & Sayeed, 2017). The effect of Tq has been proven against a variety of cancer types which include the cancer of bladder (Iskender, Izgi, & Canatan, 2016), breast (Dastjerdi, Mehdiabady, Iranpour, & Bahramian, 2016), colon (Chen et al, 2015) lung (Yang, Kuang, Lv, & Yan, 2015), and prostate (Richards, Jones, Hughes, Benghuzzi, & Tucci, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among its pharmacological properties, TQ displays antioxidant, antihistamine, immunomodulatory, anti-inflammatory, anti-microbial, and neuroprotective activities [2,[5][6][7]10,11]. It was also reported that TQ is a potent anticancer agent and has potential in the prevention and treatment of breast, colon, and ovarian cancers [4,9,10,[12][13][14].…”
mentioning
confidence: 99%